Experience of Women of Reproductive Age in Overcoming Physiological and Pathological Leucorrhoea (Fluor albus) - Khori Deskia Sapitri; Masrina Munawarah Tampubolon; Darwin Karim (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Introduction: Leucorrhoea is divided into two, namely physiological vaginal discharge and pathological vaginal discharge. About 90% of women in Indonesia have the potential to experience vaginal discharge because Indonesia is a region with a tropical climate, so that fungi easily develop which results in many cases of vaginal discharge. Many women of childbearing age lack knowledge about vaginal discharge, either physiologically or pathologically. They often think that vaginal discharge is a normal thing to experience, and apart from being embarrassed to experience vaginal discharge, women of childbearing age feel uncomfortable having to see a health professional. Research Objectives: This study aims to explore the experiences of women of childbearing age (WUS) in dealing with physiological and pathological vaginal discharge (fluor albus). Method: This study uses a qualitative research method with a descriptive phenomenological approach. Participants amounted to five people. Results: Data collection used in-depth interviews and data analysis using the Colaizzi technique. This study identified two themes, namely: 1) Physical and psychological complaints of vaginal discharge, 2) Efforts and effectiveness in overcoming vaginal discharge. Conclusion: there are differences in physical and psychological complaints experienced by participants who experience physiological and pathological vaginal discharge. How to deal with physiological vaginal discharge only requires natural medicines without medical drugs, while pathological vaginal discharge is not enough with natural medicines and requires medical treatment.